Convergent genomic diversity and novel BCAA metabolism in intrahepatic cholangiocarcinoma - Kitagawa, Akihiro; Osawa, Tsuyoshi; Noda, Miwa; Kobayashi, Yuta; Aki, Sho; Nakano, Yusuke; Saito, Tomoko; Shimizu, Dai; Komatsu, Hisateru; Sugaya, Maki; Takahashi, Junichi; Kosai, Keisuke; et al. (British journal of cancer, 2023)
Background Driver alterations may represent novel candidates for driver gene-guided therapy; however, intrahepatic cholangiocarcinoma (ICC) with multiple genomic aberrations makes them intractable. Therefore, the pathogenesis and metabolic changes of ICC need to be understood to develop new treatment strategies. We aimed to unravel the evolution of ICC and identify ICC-specific metabolic characteristics to investigate the metabolic pathway associated with ICC development using multiregional sampling to encompass the intra- and inter-tumoral heterogeneity. Methods We performed the genomic, transcriptomic, proteomic and metabolomic analysis of 39–77 ICC tumour samples and eleven normal samples. Further, we analysed their cell proliferation and viability. Results We demonstrated that intra-tumoral heterogeneity of ICCs with distinct driver genes per case exhibited neutral evolution, regardless of their tumour stage. Upregulation of BCAT1 and BCAT2 indicated the involvement of ‘Val Leu Ile degradation pathway’. ICCs exhibit the accumulation of ubiquitous metabolites, such as branched-chain amino acids including valine, leucine, and isoleucine, to negatively affect cancer prognosis. We revealed that this metabolic pathway was almost ubiquitously altered in all cases with genomic diversity and might play important roles in tumour progression and overall survival. Conclusions We propose a novel ICC onco-metabolic pathway that could enable the development of new therapeutic interventions.